A formação de professores de matemática: a tomada de consciência como interseção entre Letramento Matemático, Sequência Fedathi e a Teoria da Objetivação - Prata, Glessiane Coeli Freitas Batista (2023)
Data on external assessments present results in Mathematics proficiency and reveal that they are below expectations. This has had repercussions on research that indicates the emphasis given to literacy in Portuguese, an aspect that affects Mathematics learning in the early years of Elementary School. Another scenario that justifies the importance of this study was the promulgation of the BNCC in 2017. Initially it should be implemented in all Brazilian schools by the end of 2020. In this sense, the problem that drives this investigation is: what training is necessary for challenges regarding the continued training of teachers who teach Mathematics in classes in the early years of Elementary School from the perspective of mathematical literacy? This study works with the hypothesis that the proposal for continued training of teachers who teach Mathematics in the Initial Years of Elementary School must be based on what we call the triad (Mathematical Literacy – Fedathi Sequence – Objectivation Theory) of teacher training who teaches mathematics , through the intercession of this triad, there is awareness promoted by the spiral movement between external and internal processes. The objective is to present a proposal for continued training based on the triad composed of the intersection between mathematical literacy (LM), Objectivation Theory (TO) and the Fedathi Sequence (SF), prospecting contributions to the continued training of teachers who teach Mathematics in the Early Years of Elementary School. This study is based on authors who discuss literacy, mathematical literacy, Objectivation Theory, Fedathi Sequence and continuing teacher training. As for the research methodology, it has a qualitative approach, exploratory in nature, of the case study type. The following data collection and analysis procedures were chosen: the questionnaire, the memorial, discussion forums and, as a research strategy, the online focus group. Among the results found, we found that the conception of mathematical literacy alone would not be sufficient to meet the BNCC proposal. At this juncture, we point out that the extension course, carried out throughout this research, established itself as a training space, thus providing the opportunity for its course participants to learn about the concepts and objectives of continuing education, mathematical literacy, Fedathi Sequence and Objectivation Theory. We conclude by reaffirming our thesis that the continued training of teachers who teach mathematics in the Initial Years of Elementary School is delineated by a triad, without it the training cannot be sustained, that is, the training process does not happen in a factual way.